Auction theory - Krishna, Vijay (Academic Press is an imprint of Elsevier, 2010)
Auction Theory is the standard reference on auctions and the first source of authoritative information about multi-unit auctions.The book develops the main concepts of auction theory from scratch in a self-contained and theoretically rigorous manner.